2010
DOI: 10.1093/sleep/33.11.1495
|View full text |Cite
|
Sign up to set email alerts
|

Positive Airway Pressure Adherence in Veterans with Posttraumatic Stress Disorder

Abstract: PAP usage and adherence were lower in PTSD veterans with OSA than veterans without PTSD. Excessive sleepiness predicted PAP adherence while frequent nightmares were correlated with poor adherence to PAP therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 32 publications
1
48
0
3
Order By: Relevance
“…18 The authors found that excessive sleepiness was predictive of improved use of CPAP, while nightmares correlated with poorer CPAP adherence. Given the increased prevalence of OSA among patients with PTSD and the adverse impact of untreated OSA on clinical outcomes, understanding how PTSD affects CPAP adherence is critical.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 97%
See 2 more Smart Citations
“…18 The authors found that excessive sleepiness was predictive of improved use of CPAP, while nightmares correlated with poorer CPAP adherence. Given the increased prevalence of OSA among patients with PTSD and the adverse impact of untreated OSA on clinical outcomes, understanding how PTSD affects CPAP adherence is critical.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 97%
“…Similarly, nightmares, mask discomfort, air hunger, and claustrophobia are correlated with poor CPAP adherence among PTSD patients. 18 A recent study in an older veterans population demonstrated that CPAP adherence was signifi cantly reduced in veterans with BRIEF SUMMARY Current Knowledge/Study Rationale: There has been a dramatic rise in diagnoses of PTSD in US military combat veterans over the past decade. PTSD often coexists with both sleep-disordered breathing and insomnia, potentially worsening clinical outcomes.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to findings with MDD, the treatment of OSA through the use of CPAP reduces symptoms of PTSD and panic. [22][23][24] Unfortunately, over 50% of veterans with PTSD are non-adherent to CPAP, a significantly lower adherence rate than veterans without PTSD, 25 suggesting that PTSD itself may interfere with successful treatment of OSA.…”
Section: Osa and Anxiety Disordersmentioning
confidence: 99%
“…A retrospective study of 15 individuals with SDB and PTSD treated with continuous positive airway pressure (CPAP) therapy revealed a 75 percent improvement in nightmares and overall PTSD symptoms (Krakow et al [34]). A second study found that, although PTSD patients were less likely to adhere to recommendations concerning use of CPAP, patients with PTSD who did adhere to CPAP treatment reported decreased nightmares and improved sleep (El-Solh et al [35]). A detailed case study of a patient with SDB and PTSD treated with CPAP, with polysomnography to examine sleep architecture, demonstrated normalization of sleep architecture.…”
Section: Sleep Disordered Breathingmentioning
confidence: 99%